"I chose to become a teacher because". Exploring the factors influencing teaching choice amongst pre-service teachers in Ireland. Issue 2 (15th March 2017) - Hennessy, Jennifer; Lynch, Raymond
ABSTRACT: This study investigated the suitability of the FIT-Choice scale for use within an Irish Initial Teacher Education setting with a cohort of first year pre-service teachers ( n  = 143), from across five different subject disciplines. Exploratory factor analyses were conducted to examine participants' motivations for choosing teaching as a career, as well as their perceptions about teaching. The results were found to be consistent with the original FIT-Choice structure thus supporting the validity of the FIT-Choice scale within this Irish Initial Teacher Education context. Prior teaching and learning experiences, as well as perceived ability, were found to be the strongest influential factors in participants' decision to become a teacher. These findings further highlight the prominence given to subject-based knowledge in Ireland. The relationships between participants' motivations for becoming a teacher and their satisfaction with career choice were also examined. Choosing teaching as a fallback career was negatively related to satisfaction, whereas a desire to work with children was found to be a significant positive predictor.